Stakeholder perceptions of the competence of English education graduates - Diah Safitrhri Armin; Siti Ismahani; Siti Fitri Hasibuan; Nadhira Afifah (Institute of Information Technology and Social Science (IITSS), 2025)
This study aims to uncover the perceptions of external stakeholders regarding the competencies of graduates from the English Education Study Program (Prodi Pendidikan Bahasa Inggris) at FITK UIN SU Medan. Using a qualitative phenomenological approach, this research involved 33 external stakeholders, including school principals, agencies, and course institutions. Data were collected through online questionnaires, in-depth interviews, observations, and documentation. The results indicate that the majority of stakeholders assess the graduates of the English Education Program to possess excellent competencies, particularly in ethics, integrity, responsibility, discipline, morality, and akhlakul karimah (noble character). Additionally, the graduates were deemed to have sufficient pedagogical, professional, and social competencies to work in various fields. Interviews were conducted with five selected schools that were willing to participate. The findings of this study suggest that the study program has successfully produced graduates who are of high quality and relevant to the demands of the job market. However, there are still some aspects that need improvement, such as innovation and creativity skills. This study provides recommendations for the program to continue improving its curriculum and enhancing the quality of learning so that graduates can compete in an increasingly competitive job market.